Diastereoselective Pd-Catalyzed Domino Heck/Arylborylation Sequence Forming Borylated Chromans - Yoon, Hyung; Jang, Young Jin; Lautens, Mark (Synthesis, 2016)
A diastereoselective palladium-catalyzed domino Heck/arylborylation of aryl iodides yielding an alkylboronate containing a chroman is reported. The generated alkylpalladium(II) intermediate is intercepted with bis(pinacolato)diboron (B2pin2) in good yield as a single diastereomer.
Keywords: palladium; Heck reaction; alkylboronate; diastereoselective; chroman; benzopyran